CLINICAL RELEVANCE OF EFAVIRENZ PHARMACOKINETICS AND PHARMACOGENETICS IN HIV/AIDS THERAPY - JACOB BUNU, SAMUEL; ERE, DIEPREYE; MIEDIEGHA, OYEINTONBARA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Individuals respond to the same medications in diverse manners. Polymorphism in drug-metabolizing enzymes plays a very important role in interindividual variations in drug medical care. Hence, the aim was to review reported cases of genetic polymorphisms among the antiretrovirals, especially efavirenz, a non-nucleoside reverse transcriptase inhibitor, used in the management of human immunodeficiency virus infection/acquired immune deficiency syndrome, which is metabolized primarily by the CYP2B6 enzyme. Several previous publications on genetic polymorphism associated with the antiretrovirals of patients on highly active antiretroviral therapy were selected and carefully reviewed to evaluate their correlation and or conflict of interest among different authors. The existence of polymorphisms on the CYP2B6 gene that encodes for expression of the enzyme, among other factors responsible for efavirenz metabolism, is a significant determinant of inter-individual variability in pharmacokinetics and pharmacodynamic response to the drug used in clinical practice. Furthermore, plasma levels of efavirenz and phenotypic difference were observed, are contributing factors as to the rate of antiretroviral adverse drug reactions. Following the review, studies showed similar outcomes relating to efavirenz pharmacokinetics and polymorphism; hence, patients that display genetic polymorphism on efavirenz may likely develop the same on other therapeutic agents metabolized by the CYP450 enzymes or other polymorphic enzymes.